Crystal structure correlations with the intrinsic thermodynamics of human carbonic anhydrase inhibitor binding - Smirnov,Alexey; Zubrienė,Asta; Manakova,Elena; Gražulis,Saulius; Matulis,Daumantas (PeerJ, 2018)
The structure-thermodynamics correlation analysis was performed for a series of fluorine- and chlorine-substituted benzenesulfonamide inhibitors binding to several human carbonic anhydrase (CA) isoforms. The total of 24 crystal structures of 16 inhibitors bound to isoforms CA I, CA II, CA XII, and CA XIII provided the structural information of selective recognition between a compound and CA isoform. The binding thermodynamics of all structures was determined by the analysis of binding-linked protonation events, yielding the intrinsic parameters, i.e., the enthalpy, entropy, and Gibbs energy of binding. Inhibitor binding was compared within structurally similar pairs that differ by para- or meta-substituents enabling to obtain the contributing energies of ligand fragments. The pairs were divided into two groups. First, similar binders—the pairs that keep the same orientation of the benzene ring exhibited classical hydrophobic effect, a less exothermic enthalpy and a more favorable entropy upon addition of the hydrophobic fragments. Second, dissimilar binders—the pairs of binders that demonstrated altered positions of the benzene rings exhibited the non-classical hydrophobic effect, a more favorable enthalpy and variable entropy contribution. A deeper understanding of the energies contributing to the protein-ligand recognition should lead toward the eventual goal of rational drug design where chemical structures of ligands could be designed based on the target protein structure.
Keywords: X-ray crystallography; Structure-thermodynamics relationships; Isothermal titration calorimetry; Intrinsic thermodynamics of binding; Carbonic anhydrase inhibitors